2016
DOI: 10.1161/atvbaha.116.307559
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Depletion Promotes Aortic Infiltration of Immunosuppressive Cells and Is Protective of Experimental Aortic Aneurysm

Abstract: Objective B cell depletion therapy is widely used for treatment of cancers and autoimmune diseases. B cells are abundant in abdominal aortic aneurysms (AAA), however, it is unknown whether B cell depletion therapy affects AAA growth. Using experimental models of murine AAA, we aim to examine the effect of B cell depletion on AAA formation. Approach and Results Wild-type or Apolipoprotein E knockout mice were treated with mouse monoclonal anti-CD20 or control antibodies and subjected to an elastase perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 36 publications
(49 reference statements)
1
55
0
Order By: Relevance
“…In Apoe ‐deficient or Ldlr ‐deficient hyperlipidemic mice, AAA can be induced with a continuous infusion of angiotensin II. Our finding that B cells were required for the full development of AAA after CaCl 2 challenge was consistent with previous reports that showed that muMT mice were protected from elastase‐induced AAA and that B cell depletion by anti‐CD20 antibody abrogated AAA development induced by angiotensin II in Apoe ‐deficient mice . On the other hand, a state of total lymphocyte deficiency attenuated atherosclerosis in Apoe ‐deficient mice but not angiotensin II–induced AAA; furthermore, muMT mice were not protected from elastase‐induced AAA .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In Apoe ‐deficient or Ldlr ‐deficient hyperlipidemic mice, AAA can be induced with a continuous infusion of angiotensin II. Our finding that B cells were required for the full development of AAA after CaCl 2 challenge was consistent with previous reports that showed that muMT mice were protected from elastase‐induced AAA and that B cell depletion by anti‐CD20 antibody abrogated AAA development induced by angiotensin II in Apoe ‐deficient mice . On the other hand, a state of total lymphocyte deficiency attenuated atherosclerosis in Apoe ‐deficient mice but not angiotensin II–induced AAA; furthermore, muMT mice were not protected from elastase‐induced AAA .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, a state of total lymphocyte deficiency attenuated atherosclerosis in Apoe ‐deficient mice but not angiotensin II–induced AAA; furthermore, muMT mice were not protected from elastase‐induced AAA . A potential explanation for these controversial results could be that T cells participated in AAA pathogenesis by modulating the effect of B cells . For example, the deletion of all T cells has been reported to abrogate the effect of regulatory T cells in suppressing AAA formation in an angiotensin II–induced model .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Consistent with this finding, Ailawadi’s group reported that depletion of B cells by anti-CD20 antibody reduced AAA in both AngII-induced and elastase-induced AAA models. 42 …”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%